2008
DOI: 10.5194/acpd-8-11967-2008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Saharan dust levels in Greece and received inhalation doses

Abstract: Abstract. The desert of Sahara is one of the major sources of mineral dust on Earth, producing around 2×108 tons/yr. Under certain weather conditions, dust particles from Saharan desert get transported over the Mediterranean Sea and most of Europe. The limiting values set by the directive EC/30/1999 of European Union can easily be exceeded by the transport of desert dust particles in all south European areas and especially urban. In this study, the effects of dust transport on air quality in several Greek urba… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 34 publications
4
20
0
4
Order By: Relevance
“…We showed that it originated in the long-range transport of African dust, confirming that outbreak phenomena can influence particle levels in southern France even under the form of moderate episodes. This result is in agreement with the observations reported for other Mediterranean countries (Rodriguez et al, 2001(Rodriguez et al, , 2002Querol et al, 2009;Mitsakou, 2008). Although the CHIMERE model was able to reproduce the nature and the timing of this episode, we show that the use of climatological values to determine the amount of dust transferred to the domain from the larger scale are insufficient to reproduce the amplitude of the event.…”
Section: Discussionsupporting
confidence: 78%
“…We showed that it originated in the long-range transport of African dust, confirming that outbreak phenomena can influence particle levels in southern France even under the form of moderate episodes. This result is in agreement with the observations reported for other Mediterranean countries (Rodriguez et al, 2001(Rodriguez et al, , 2002Querol et al, 2009;Mitsakou, 2008). Although the CHIMERE model was able to reproduce the nature and the timing of this episode, we show that the use of climatological values to determine the amount of dust transferred to the domain from the larger scale are insufficient to reproduce the amplitude of the event.…”
Section: Discussionsupporting
confidence: 78%
“…The main distinctive feature of PM at the three sites of this study is the relatively high levels of the crustal component (4 and 1 µg/m 3 for PM 10 and PM 2.5 at MSY; 14 and 2 (0.8 if the major 6 dust events are removed) µg/m 3 for PM 10 and PM 1 at FKL; and 9, and 1 µg/m 3 for PM 10 and PM 2.5 at ERL, respectively) when compared with the selected central and northern European sites (2 and <0.5 µg/m 3 for PM 10 and PM 2.5 in most cases). The accessional year round con- tribution of dust at FKL is estimated to be 8±5 µgPM 10 /m 3 , in agreement with the range given by Mitsakou et al (2008) (5-9 µg/m 3 ) for Heraklion, the nearest large city to FKL station. Of course, at the remote site of FKL the percentage contribution of dust is much higher than at Heraklion reaching 40-50% in spring (frequent dust outbreaks) and winter (some of which are among the most intense events).…”
Section: Pm Speciationsupporting
confidence: 67%
“…However, these tools alone are in general not sufficient as the transit of air masses coming from Sahara does not necessarily imply high PM concentrations at ground level. A modelbased method has been proposed by Mitsakou et al (2008) to estimate the contribution of desert dust to PM10 in Greece, while other approaches focused on the analysis of PM10 concentration time sequences (Ganor et al, 2009). During the last decade several papers appeared in the literature concerning the desert dust contribution to PM in Spain (see for example Rodriguez et al, 2001;Escudero et al, 2005Escudero et al, , 2007Querol et al, 2009).…”
Section: Introductionmentioning
confidence: 99%